Four-Element Biodegradable Substrate-Integrated MIMO DRA with Radiation Diversity - Rasika Verma; Rohit Sharma (Journal of Electromagnetic Engineering and Science, 2024)
This article presents a four-element directional multiple input multiple output (MIMO) rectangular dielectric resonator antenna (RDRA) equipped with strategically placed copper reflector plates to enhance port isolation. This design aims to achieve an extended coverage range without compromising the coverage area. The proposed MIMO antenna is 3D printed using biodegradable polylactic acid to ensure mechanical robustness and then integrated with the substrate to prevent mis-mounting issues. The proposed design exhibits good MIMO characteristics, registering a 3-GHz bandwidth (4–7 GHz) for |S11|≤−10 dB and a minimum radiation gain of 7 dBi for all four RDRAs. The antenna demonstrates a rotation of radiation patterns for different ports, thus enabling beam formation in specific directions. With a beam width of 71.2°, the antenna covers all directions without any fade zones. The proposed 3D printed antenna offers simplicity, strong MIMO properties, and practicality for wireless communication systems, making it suitable for industrial, scientific, and medical band applications.